Genetic Study in a Case of Birt-Hogg-Dubé Syndrome - Park, Geon (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2011)
Birt-Hogg-Dubé syndrome (BHDS) is an autosomal dominantly inherited disorder characterized by multiple trichodiscomas, fibrofolliculomas, and acrocordons. There is also an increased risk of developing renal neoplasms and lung cysts/spontaneous pneumothorax. We present a 43-year-old man with multiple, 2~4 mm sized, dome-shaped, and skin-colored papules on his cheek and neck. On the basis of clinical finding and histopathologic examination on the cheek lesion, it was diagnosed as multiple trichodiscomas. Subsequently, molecular analysis revealed a mutation in the folliculin gene. We report a rare case of BHDS with a proved gene mutation.